Caracterização de crianças e adolescentes com transtorno do espectro do autismo em centros de atenção psicossocial infantojuvenis (CAPSij) - Silva, Rafaela Pereira (Universidade Federal de São Carlos, 2019)
The understanding of autism, currently known as Autism Spectrum Disorder (ASD), has undergone several changes over the years. In the Diagnostic and Statistical Manual of Mental Disorders (DSM-III), in 1980, came the inclusion of autism as Pervasive Developmental Disorders (PDD). However, in the tenth revision from the International Classification of Diseases (ICD-10) from the World Health Organization (1992), it included childhood autism inside the global developmental disorders group. At the DSM-IV (1994), in addition to autism, was the inclusion of the Asperger syndrome and Pervasive developmental disorder not otherwise specified, and, in the fifth and latest version (DSM-V), from 2013, the denomination used was "autism spectrum disorder"; besides changing the denomination, occurred the modification in the structure of symptoms and signs group that determinates the diagnosis of ASD. In Brazil, philanthropic institutions within social services or autistic family associations are often responsible for the care of these children with autism. Some studies show that this late development caused the elaboration of the public policy for autism to be marked by two opposing groups: the group linked to the actions from the psychosocial attention related to the public policy of the unified health system (SUS), and the group associations of parents and family members of autistic people. With SUS public policies, were created the Child and Youth Psychosocial Care Centers (CAPSij) with the perspective of territorial health and articulation with the Psychosocial Care Network (RAPS). Recent studies address the difficulties encountered in these CAPSij concerning strategies and actions aimed at these children and adolescents with autism, highlighting the need for research to assist in the identification and understanding of the demands that reach these services. The current study aimed to characterize people with autism-linked to a CAPSij in a town in the state of São Paulo. It is an exploratory research of a quantitative approach that involved the participation of managers from all four Child and Youth Psychosocial Care Centers (CAPSij) from a town in the state of São Paulo. For data collection, modules of a structured interview script were used, elaborated in the broader research to which this TCC is linked, and a medical record data record form, elaborated in this study. It revealed that 26% of the CAPSij patients were autists, with a prevalence of reach between 1 and 5 years old, mostly males. The study also identified some weaknesses in the engagement of adolescents with ASD in these services. In general, the results achieved revealed fragilities resulting from the team composition in CAPSij, that should impact the care practices and actions related to ASD in particular.
Characterization of children and adolescents with autism spectrum disorder in children and youth psychosocial care centers (CAPSij)
Keywords: Autismo; Saúde mental; Adolescente; Psicossocial; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL